Research on Food Safety and Security of Cold Chain Logistics. Issue 1 (January 2021) - Yu, Zexia; Liu, Yinkai; Wang, Qinghui; Sun, Lei; Sun, Shuangyan
Abstract: Fresh fruits and vegetables are the necessities of daily life and provide rich nutrients for people's daily life. As the country with the largest population, the annual consumption of seasonal agricultural products, dairy products and aquatic products in China is huge. With the continuous development of e-commerce, the transportation and circulation of fresh fruit has become more extensive. However, there are still some hidden dangers in the cold chain logistics of food in our country, and the safety problems such as pollution, deterioration and decay of agricultural products in the course of transportation also lead to serious loss of commodities, and the problem of food safety can not be guaranteed.According to the relevant data, the annual loss of fresh fruits and vegetables in transit in China in the world ranking is very high.Therefore, the rapid development of science and technology in recent years and the demand for the transportation of fresh fruits and vegetables have greatly improved the transportation conditions of fresh fruits and vegetables.In view of this problem, this paper analyzes the problem of food safety in cold chain logistics in China and puts forward relevant safeguard measures